ISLAM DAN FILOSOFI MASYARAKAT FAKFAK - Mohamadon D.Husen (STAI Syubbanul Wathon Magelang, 2018)
Fakfak community is known as religious society, friendly, goodmanners, maintaining tolerance among religious people, appreciatingunity and unity because everything is contained in the philosophy andoutlook of life. Philosophy of society Fakfak is a life view that wasexcavated and formed based on mutual consensus that contains thenoble values of the people of Fakfak itself since time immemorial whichthen used as a bond and then the philosophy or life view is used as aguide and even motivation in running various aspects people's lives.The philosophy contains a substance where all attitudes and worldviewsare based on